# Please Can You Help Solve 3(x-2)-2x=x-6?

This is an easy question. Here is the solution:
3(x-2)-2x=x-6
3x - 6 - 2x = x - 6
3x - 2x - 6 = x - 6
x- 6 = x - 6
Hence proved that right hand side of the equation is equal to the left hand side of the equation.
thanked the writer.
Emraan Varshani commented
rayoflight, you cannot proved left and right as derived above, because that can be done only in the cases where you aren't able to solve further..however in this case you can reach to final ans, so basically your ans is 0
Solve for x.

X - (2x - 6) = 3x - 2(x + 5)
thanked the writer.
This equation can't be solved as left hand side and the right hand side are the same forms of a particular expression. There have to be two different expressions in x on both sides of the equation to be able to solve it.
Eg., we can't solve x+9=x+9.   We know this equation is true, but we can't find the value of x.
Or we can even say that the answer to your question is any value between -infinity to +infinity.   As any value of x will satisfy the equation.
thanked the writer.
Very simple, just apply the BODMAS RULE;
first open the bracket by multiplying each numbers
like as follow;
3(x-2)-2x=x-6
3x - 6 - 2x = x - 6
Now take x variable on one side and constants on the other.
3x - 2x - x = -6 + 6 when x, -6 comes across "=", its signs changes.
So 3x - 3x = - + 6
therefore 0 = 0
hence the ans is "0".
And yes even you cannot proved left and right as derived by "rayoflight ", because that can be done only in the cases where you aren't able to solve further..however in this case you can reach to final ans, so basically your ans is 0
thanked the writer. 